Research progress in the correlation between chronic stress and ovarian dysfunction - WEI Liutong; LAI Dongmei (Shanghai Jiaotong Daxue xuebao. Yixue ban)
The ovary is an important reproductive organ for women. Decreased ovarian function not only affects the reproductive capabilities, but also leads to the decline of women′s quality of life. Recent studies have shown that chronic stress affects the hypothalamic-pituitary-ovary axis directly or indirectly and leads to ovarian dysfunction-including excessive activation of primordial follicles, a reduction in preantral and preovulatory follicles, decline of oocyte quality, and granulosa cell apoptosis, through corticotropin-releasing hormone, corticosterone and cortisol secreted by the hypothalamic-pituitary-adrenal axis, as well as epinephrine and norepinephrine released by the sympathetic-adrenal-medullary axis and sympathetic nervous system. This article reviews the correlation between chronic stress and ovarian dysfunction, along with the potential mechanisms.